Radius and Differential Subordination Results for Starlikeness Associated with Limaçon Class - Afis Saliu; Kanwal Jabeen; Isra Al-shbeil; Semiu Oladipupo Oladejo; Adriana Cătaş (Journal of Function Spaces)
In this study we investigate the sharp radius of starlikeness of subclasses of Ma and Minda class for the ratio of analytic functions which are related to limaçon functions. This survey is connected also to the first-order differential subordinations. In this context, we get the condition on β for which certain differential subordinations associated with limaçon functions imply Ma and Minda starlike functions. Simple corollaries are provided for certain examples of our results. Finally, we present several geometries related to our study.